Physical Activity in Normal Technical Secondary School Students in Singapore - Swee, Sarah Wan Jun (2017)
Purpose: To compare physical activity in Singaporean Normal Technical Secondary School students between genders and international guidelines and to examine the relationship between physical activity and socioeconomic status. Methods: 48 participants (28 males, 20 females; Mage = 13.46, SDage = .54) completed self-reporting questionnaires regarding physical activity perceptions and engagement. Their parents completed one regarding their socioeconomic status. Participants then wore wrist-worn accelerometers for 7-days consecutively. Based on an exclusion criterion of calibration error and non-wear time, 32 participants (13 males, 19 females; Mage = 13.34, SDage = .48) remained. Results: Moderate-to-vigorous physical activity was viewed in minimum 10-minute bouts and without bouts. With bouts, males engaged in significantly more than females (Mmales = 23.20, SDmales = 19.37, Mfemales = 10.72, SDfemales = 9.66; t(30) = 2.416, p = .022), both genders did not meet international guidelines and no correlation between socioeconomic status and physical activity was observed (R2 = .131, Adjusted R2 = .071, F(2,29) = 2.189, p = .130). Without bouts, participants met international guidelines, there was no significant gender difference (Mmales = 142.79, SDmales = 45.27, Mfemales = 135.93, SDfemales = 35.55; t(30) = .479, p = .635) and no correlation between socioeconomic status and physical activity (R2 = .125, Adjusted R2 = .064, F(2,29) = 2.062, p = .145). Conclusion: The importance of physical activity in bouts should be established. Furthermore, it is important for future studies to span across different schools and academic streams to establish if the study’s findings are generalizable to a larger population.